2001
DOI: 10.1046/j.1365-3059.2001.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction ofPhytophthora infestanson tubers of potato cultivars with different levels of blight resistance

Abstract: Differential interactions in tuber blight attack between potato cultivars and Phytophthora infestans isolates were studied using whole tuber and tuber slice assays. Tuber blight incidence and severity were studied in a whole tuber assay, whilst necrosis and mycelium coverage were evaluated in a tuber slice assay. The overall defence reaction of the potato cultivars tested varied considerably. Cultivars like Kartel and Producent showed resistant reactions, whilst Bintje and, to a lesser extent, Astarte reacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 34 publications
1
40
0
1
Order By: Relevance
“…Expression of tuber resistance depends on the tissue inoculated (Jwieryjski and Zimnoch-Guzowska 2001). The tuber skin and the cambial layer just underneath the tuber skin can be important barriers for infection (Toxopeus 1958(Toxopeus , 1961, but the periderm, cortex and medulla can also be involved in tuber resistance (Flier et al 2001). Recently, Park et al (2005c) showed that the genes Rpi-abpt and R3a are foliage-speciWc, while R1 or R1-like is eVective both in tubers and foliage, conWrming previous Wndings of Roer and Toxopeus (1961), who also investigated the eVects of R1 and R3 on tuber resistance.…”
Section: Discussionsupporting
confidence: 53%
“…Expression of tuber resistance depends on the tissue inoculated (Jwieryjski and Zimnoch-Guzowska 2001). The tuber skin and the cambial layer just underneath the tuber skin can be important barriers for infection (Toxopeus 1958(Toxopeus , 1961, but the periderm, cortex and medulla can also be involved in tuber resistance (Flier et al 2001). Recently, Park et al (2005c) showed that the genes Rpi-abpt and R3a are foliage-speciWc, while R1 or R1-like is eVective both in tubers and foliage, conWrming previous Wndings of Roer and Toxopeus (1961), who also investigated the eVects of R1 and R3 on tuber resistance.…”
Section: Discussionsupporting
confidence: 53%
“…The tuber skin and the layer just below the tuber skin (inoculated in whole tuber tests) form two diVerent, important barriers for the late blight infection (Toxopeus 1958(Toxopeus , 1961. However, cortex and medulla (inoculated in slice tests) can also be involved in resistance mechanism (Flier et al 2001). Three resistance components: leaXet, slice and whole tuber resistance showed normal distribution in population 98-21 ( Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Three major components are known to contribute to late blight resistance in tubers; 1) a physical barrier consisting of several layers of phloem cells, known the periderm; 2) the outer cortical cell layers that retard the growth of lesions and can completely block hyphal growth; and 3) medulla storage tissues which can reduce hyphal growth and sporulation of P. infestans (Flier,Turkensteen, & Mulder, 1998;Flier, Turkensteen,Van den Bosch, Vereijken, & Mulder, 2001;Pathak & Clarke, 1987). Furthermore, immature tubers are more susceptible to tuber blight than mature tubers (Grinberger, Kadish, & Cohen, 1995), which means that assayed tubers should be of similar age.…”
Section: Discussionmentioning
confidence: 99%